KEBIJAKAN PEMERINTAH DAERAH PEMINDAHAN PASAR RAWAJAYA KE PASAR WOSIA (STUDI KASUS DI KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA) - Ibnu Kanaha (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The purpose of this research is to know and analyze Local Government Policy in Rawajaya Market Transfer to Wosia Market. The research method is qualitative descriptive. Technique of completion of interview data, observation, and documentation. Data analysis using. The research finds commitment in its development is still very low quality. This finding is still lacking to anticipate obstacles that hamper violence against pendangang, the socialization policy, the policy is not maximal. Not strict in the form of policy, for example there is still sales in the market rawajaya. The government returns or improves the content of the message if it does not sell again in the market rawajaya. Governments can change and can contribute to thinking in policy, the government creates the market of Wosia.